Prevalence, management, and prediction of venous access site occlusion in patients undergoing lead revision surgery. (15th June 2023) - Kellnar, Antonia; Fichtner, Stephanie; Reitinger, Philipp; Sadoni, Sebastian; Heyn, Oliver; Sams, Lauren; Estner, Heidi L.; Lackermair, Korbinian
Abstract: Background: Implantable electronic cardiac devices (CIED) have emerged as an essential component in the treatment of cardiac arrhythmias and heart failure. Due to increased life expectancy, expanding indications and limited technical survival, an increasing number of revision procedures can be anticipated. Venous access site occlusion (VASO) is the main obstacle during revision surgery. In this retrospective study we evaluated the prevalence, predictive parameters and operative management of venous access site occlusion. Methods and results: Between 01/2016 and 12/2020 304 patients underwent lead revision surgery of transvenous CIED in our department. Prevalence of VASO was 25.7% ( n = 78), one patient was symptomatic. Independent predicting clinical parameters were male sex (2.86 (1.39–5.87), p < 0.01) and lead age (1.11 (1.05–1.18), p < 0.01)). Revision surgery despite VASO was successful in 97.4% ( n = 76) without prolongation of the total surgery time or higher complication rates. Yet, lead extraction was possible in 92% of patients with VASO vs. 98.2% of patients without VASO (p 0.01). Conclusion: VASO is a frequent condition in patients undergoing lead revision surgery, but successful revision is feasible in most cases without preceding lead extraction. However, the lower success rates of lead extractions may be prognostically relevant, especially for younger patients. Highlights: One quarter of patients undergoing lead revision reveal venous access site occlusion. Independent predictors of venous access site occlusion are male sex and lead age. Despite venous access site occlusion lead revision is successful in 97.4% of patients. However, lead extraction is significantly less feasible in case of venous occlusion.